Endosomal Cholesterol in Viral Infections – A Common Denominator? - Glitscher, Mirco; Hildt, Eberhard (Frontiers in Physiology, 2021)
Cholesterol has gained tremendous attention as an essential lipid in the life cycle of virtually all viruses. These seem to have developed manifold strategies to modulate the cholesterol metabolism to the side of lipid uptake and de novo synthesis. In turn, affecting the cholesterol homeostasis has emerged as novel broad-spectrum antiviral strategy. On the other hand, the innate immune system is similarly regulated by the lipid and stimulated by its derivatives. This certainly requires attention in the design of antiviral strategies aiming to decrease cellular cholesterol, as evidence accumulates that withdrawal of cholesterol hampers innate immunity. Secondly, there are exceptions to the rule of the abovementioned virus-induced metabolic shift towards cholesterol anabolism. It therefore is of interest to dissect underlying regulatory mechanisms, which we aimed for in this minireview. We further collected evidence for intracellular cholesterol concentrations being less important in viral life cycles as compared to the spatial distribution of the lipid. Various routes of cholesterol trafficking were found to be hijacked in viral infections with respect to organelle-endosome contact sites mediating cholesterol shuttling. With this in mind, it presents rational to focus research in understanding these mechanisms in more detail. As a final aim, a pan-antiviral treatment could be found just within the transport and re-adjustment of local cholesterol concentrations. Thus, we aimed to emphasize the importance of the regulatory roles the endosomal system fulfils herein and hope to stimulate research in this field.